Historiografi Blambangan: Akulturasi Hindu-Islam Dalam Nisan, Babad, Dan Tradisi Abad 19 Masehi - Abdur Rahman; Miftahul Khoiri; M. As Sabiq Bis Sunan; Viona Aurillia Putri (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
Blambangan, which is the easternmost region of Java Island, has a long history as the last Hindu stronghold in Java and serves as an important transitional space in the process of Islamization. This research aims to reveal how the process of religious blending occurred, as well as how local historical narratives represent this blending in the form of tombstones, babad (chronicles) texts, and oral traditions. Through a qualitative approach using historical methods divided into Heuristics, Criticism, Interpretation, and Historiography. This study finds that the blending process of Hinduism and Islam was a form of cultural acculturation that took place peacefully and continuously. The political transition from local kingdoms to colonial rule also encouraged the transformation of the local community’s religious and cultural identity. The spread of Islam did not completely erase the Hindu cultural heritage but instead occurred within a harmonious framework of acculturation. This is evident in religious practices, customs, architecture, and social systems that combine Hindu elements with Islamic values. The spatial layout of the city of Banyuwangi, the establishment of the Great Mosque Baiturrahman, as well as the existence of tombstones with Arabic-Pegon inscriptions. Local historiography, such as the Babad Blambangan, along with colonial records and archaeological findings, reinforces the narrative that the Hindu-Islam blending in Blambangan was not merely a process of religious conversion, but rather a complex socio-cultural transformation.